The Influence of Green Practices and Green Perceived Value on Green Loyalty through Green Satisfaction with Gender as a Moderating Variable - Riesya Nabiela Rahma Putri; Titis Miranti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study wants to show the connection between green practices implemented by Islamic banks, green perceived value, and customer loyalty, either directly or through green satisfaction, and gender as a moderating variable. To answer the research hypothesis, 202 questionnaires that have been distributed to Sharia commercial bank customers in Indonesia were analyzed in this study. Sample determination was carried out through a purposive sampling technique. Structural Equation Modeling – Partial Least Square (SEM-PLS) was used to analyze the data. This research found that green practice does not significantly affect green loyalty but significantly affects green satisfaction. Meanwhile, green perceived value directly makes customers loyal and satisfied with Sharia banks. It also discovered that green satisfaction has a significant effect on green loyalty and can mediate the influence of green practices and perceived value on green loyalty. At the same time, gender as a moderating variable cannot moderate the influence of green practices and perceived value on green loyalty. This research emphasizes the importance of innovation and developing practices that positively impact the environment and are satisfying because this program can increase customers' loyalty towards Sharia banking.